A randomized controlled trial comparing laparoscopic lens defogging techniques through simulation model - Vijay Palvia; Aaron J Herrera Gonzalez; Richard S Vigh; James N Anasti (Gynecology and Minimally Invasive Therapy, 2018)
Context: Current literature demonstrates a lack of comparative studies regarding effective techniques for reducing laparoscopic lens fogging. Aim: Our primary objective is to determine the efficacy of various laparoscopic defogging techniques (LDT) through a randomized controlled trial that employs a novel simulation model of the abdominopelvic cavity. Settings and Design: This study was conducted at academic community hospital. This study design was a randomized controlled trial through simulation. Subjects and Methods: A chamber was constructed that simulated the abdominopelvic cavity. We used 5 and 10 mm 0° laparoscopes. A 10 cm visual analog scale was developed to assign visual clarity (VC) scores. The 10 cm mark indicated perfect VC. We employed the following LDTs: (1) glove warming (GLOVE), (2) surfactant solution (Fog Reduction and Elimination Device [FRED]), (3) chlorhexidine solution (SOAP), (4) warm saline (SALINE), and (5) control. Three observers were blinded to the LDT used. Primary outcomes included VC scores at designated time intervals (5, 30, and 60 s) for each LDT. A minimum of 10 observations per time interval were required to achieve adequate power based on a 2.5 cm difference in VC scores. Results: For the 10 mm laparoscope, FRED, SOAP, and SALINE had a VC score at 60 s (VC60) higher than control (4.8 ± 2.2, 7.8 ± 0.8, 7.9 ± 0.7 vs. 2.4 ± 0.72, P < 0.05). Both SOAP and SALINE VC60 scores were higher than FRED (7.8 ± 0.8, 7.9 ± 0.7 vs. 4.8 ± 2.2, P < 0.05). No differences were noted in VC60 scores between control and GLOVE (2.4 ± 0.72 vs. 3.1 ± 2.2, P > 0.05) and between SOAP and SALINE (7.8 ± 0.8 vs. 7.9 ± 0.7, P > 0.05). Similar results were noted with the 5 mm laparoscope. Conclusions: Common LDTs such as SALINE and SOAP were more effective than FRED, while GLOVE was no different than control. These results demonstrate that the use of effective LDTs can potentially translate into improved patient care and operative outcomes during surgery.